Oral Antibacterial Drug Prescribing in Primary Care Out-of-Hours Services: A Scoping Review - Sarah Khalid Al Hussain; Rhian Deslandes; Deborah Edwards; Karen Louise Hodson (Antibiotics)
Background/Objectives: The rapid spread of antimicrobial resistance (AMR) presents a critical threat to global health. Primary care plays a significant role in this crisis, with oral antibacterial drugs among the most prescribed medications. Antibacterial prescribing rates are often high and complicated in out-of-hours (OOH) services, including weekdays outside regular hours, weekends, and holidays, potentially exacerbating AMR. This review aims to identify the existing literature on oral antibacterial drug prescribing within primary care OOH services. Methods: This review followed established frameworks, adhered to PRISMA-ScR guidelines, and the protocol was registered on Open Science Framework. Seven databases were searched from 2017 to May 2022. Data were summarised, tabulated, and presented narratively to explore themes and patterns that aligned with the review objectives. Results: The search identified 28 studies from nine high-income countries, mainly the UK (n = 6) and Belgium (n = 5). Most were quantitative studies (n = 23). Key areas identified included common oral antibacterial prescriptions, prescribing trends, presentations and conditions managed in OOH services, factors and predictors associated with prescribing, prescribing appropriateness, the impact of interventions on prescribing, prescribing in the context of COVID-19, patient satisfaction and expectations, and the challenges encountered, such as factors influencing prescribing behaviour and decision making, safety netting, and communication. Conclusions: This review highlights key areas around oral antibacterial prescribing in primary care OOH services. Despite the numerous articles identified covering various areas within OOH services, the variability in OOH services approaches across countries and studies complicates the comparison of practice. Further research is needed to better understand practices in these settings.